Cushing’s syndrome diagnosed after delivery: a case report - Andjelkovic, Marija V.; Mladenovic, Violeta S.; Djukic, Aleksandar Lj; Jankovic, Slobodan M. (Central European journal of medicine, 2013)
Introduction During normal pregnancy there are significant changes in hypothalamic-pituitary-adrenal axis, with increased levels of plasma cortisol and adrenocorticotropic hormone which sometimes reach values observed in patients with Cushing’s syndrome. Cushing’s syndrome (CS) is rarely encountered during pregnancy, but is associated with serious maternal and fetal complications. Case presentation A 31-year-old female was admitted to our institution four weeks after delivery. Physical examination revealed moon face, purple striae throughout the abdomen, bruising over the legs, a dorsocervical fat pad and hirsutism. She delivered a eutrophic preterm newborn at 34 weeks gestation, without any maternal or fetal complications during delivery. Imaging showed a mass in the right suprarenal gland with a normal pituitary. After four weeks the patient underwent a right adrenalectomy. The mass was eventually identified as an adrenocortical adenoma. Conclusion In our case the diagnosis of CS was established only after pregnancy, which enabled the development of numerous adverse consequences secondary to increased plasma cortisol. If CS is recognized during pregnancy, treatment and its timing could be carefully chosen according to the patient’s individual characteristics.